Maintenance azacitidine after myeloablative allogeneic hematopoietic cell transplantation for myeloid malignancies. Issue 12 (2nd December 2018) - Maples, Kathryn T.; Sabo, Roy T.; McCarty, John M.; Toor, Amir A.; Hawks, Kelly G.
Abstract: Allogeneic hematopoietic cell transplantation (HCT) is a curative option for patients with acute myeloid leukemia (AML) and myelodysplastic syndrome (MDS), but carries a high risk of relapse. This retrospective review evaluates the effectiveness of maintenance azacitidine in high-risk AML and MDS patients to reduce the probability of relapse. Twenty-five patients who received maintenance azacitidine were matched to historical controls in a two-to-one ratio based on diagnosis, donor type, conditioning regimen intensity, and age. Over 90% of patients received myeloablative conditioning. There was no difference in time to hematologic relapse, overall survival, or non-relapse mortality. Maintenance therapy was stopped early in 72% of patients due to graft-versus-host-disease, relapse, infection, and intolerance (13 of 25 patients received less than 4 cycles). There was a trend towards higher toxicity in the azacitidine group. The use of prophylactic azacitidine following myeloablative allogeneic HCT outside a clinical trial cannot be recommended at this time.